Effects of dietary propolis on the number and size of pleopadal egg, oxidative stress and antioxidant status of freshwater crayfish (Astacus leptodactylus Eschscholtz) - Yonar, Serpil Mise; Koprucu, Kenan; Yonar, Muhammet Enis; Silici, Sibel (Elsevier, 2017)
Four different crayfish diets; control, El, E2 and E3, respectively containing 0, 1, 2 and 4% propolis, were tested to determine the effects of dietary propolis on the number and size of pleopadal egg, and malondialdehyde (MDA) level, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) activities in the freshwater crayfish (Astacus leptodactylus). The crayfish were kept at 9.6 +/- 5.3 degrees C water temperature and fed three times daily during a six month period The pleopodal egg number (from 7 to 9) produced per gram of the bpdy weight and total pleopodal egg number (from 201 to 263) significantly increased (P < 0.05) with the dietary propolis supplementation. However, an increase in the dietary propolis led to a significant decrease (P < 0.05) in the pleopodal egg size (from 3.22 mm to 2.76 mm). MDA level significantly (P < 0.05) decreased in the hepatopancreas (from 4.78 to 3.04 nmol/g protein) and ovarium (from 3.52 to 1.98 nmol/g protein) of the crayfish fed with the increased dietary propolis level. On the other hand, an increase in the dietary propolis led to a significant increase (P < 0.05) in SOD activities in hepatopancreas (from 21.8 to 41.1 U/g protein) and ovarium (from 16.8 to 26.8 U/g protein). However, CAT activities significantly decreased (P < 0.05) in the hepatopancreas (from 23.8 to 18.9 nmol/g protein) and ovarium (from 21.8 to 17.5 nmol/g protein) of the crayfish fed with the increased dietary propolis level. Similarly, an increase in the dietary propolis caused a significant decrease (P < 0.05) in GSH-Px activities in the hepatopancreas (from 21.8 to 41.1 U/g protein) and ovarium (from 16.8 to 26.8 U/g protein) with the formation of the pleopodal egg. The dietary propolis improves reproductive efficiency in the crayfish and decreases the oxidative stress under controlled hatchery conditions.
Keywords: Antioxidant enzyme; Freshwater crayfish; Diet; Oxidative stress; Pleopadal egg; Propolis